Three Dimensional Quality Assessments of Applied Pelvic Binders - Peyman Bakhshayesh; David Hullberg Risling; Anders Enocson (Bulletin of Emergency and Trauma, 2019)
Objective: To assess the quality of applied pelvic binders using three dimensional computer tomography (3D CT).Methods: A local trauma registry was used to identify patients with pelvic fractures after high-energy trauma during 2011-2015. A 3D CT reconstruction was made from the initial trauma computer tomography images to assess the level of application, symmetricity of the binder and achieved fracture reduction. An acceptable application of the pelvic binder was deemed if it was at the trochanteric level, symmetric and minimized residual displacement.Results:  We found 73 patients with a pelvic fracture and a pelvic binder on the initial trauma CT-scan. The mean (±SD) age of the patients was 46±17 years and 40% (n=29) were females. The median ISS score was 38 (IQR;29-50), the mean systolic blood pressure on arrival was 106±46 mmHg and the median GCS on arrival was 14 (IQR;7-15). We found that 59% (n=43) of the binders were correctly applied (symmetric at the trochanteric level, symmetrical and with acceptable residual displacement of the fracture). The 30-day mortality was higher in patients with non-correct application 17% (n=5/30) compared to patients with correct application of the pelvic binder 9.3% (n=4/43) however this was not statistically significant (p=0.562).Conclusion: A substantial number of patients had non-correct application of pelvic binders. Future studies using 3D technique are encouraged to further investigate clinical impacts of non-appropriate application of pelvic binders.